Cemented Versus Noncemented Total Knee Arthroplasty Outcomes. Issue 6 (15th March 2022) - Stavrakis, Alexandra; Arshi, Armin; Chiou, Daniel; Hsiue, Peter; Horneff, John Gabriel; Photopoulos, Christos
Abstract : Introduction: Aseptic loosening remains one of the most common indications for revision total knee arthroplasty (TKA). Given the demographic shift to a younger and more active TKA patient population, some surgeons have revisited noncemented fixation given its potential for lower rates of long-term aseptic loosening. The purpose of this study was to compare the demographics and complications between patients undergoing noncemented and cemented TKA. Methods: Using the MKnee subset of the PearlDiver database, diagnosis and procedure codes were used to identify patients who had undergone cemented or noncemented TKA for osteoarthritis with a minimum 2-year follow-up. Propensity score matching was done to compare risk-adjusted medical and surgical complication profiles at 90 days, 1 year, and 2 years. Results: Of 203, 574 patients identified, 3.2% underwent noncemented TKA and 96.8% underwent cemented TKA. Using propensity-matched analysis, there was no difference in 90-day medical complications. Noncemented TKA was associated with a greater risk of periprosthetic joint infection throughout the study (90-day odds ratio [OR] 1.34, 1-year OR 1.27, 2-year OR 1.27, P < 0.05). Noncemented TKA was associated with a greater risk of periprosthetic fracture at 1 year and 2 years (1 year OR 2.19, 2 years OR 1.89, P < 0.05). No notable difference was observed in risk of aseptic loosening between the two groups. Discussion: Noncemented TKA is associated with a higher rate of periprosthetic joint infection and periprosthetic fracture. Additional studies are needed to compare long-term rates of aseptic loosening between noncemented and cemented TKA. Level of Evidence: Level III